Hadith #577 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
I asked Sulaiman b. Yasar whether the semen that gets on to the garment of a person should be washed or not. He replied: A’isha told me: The Messenger of Allah (ﷺ) washed the semen, and then went out for prayer in that very garment and I saw the mark of washing on it.
Grade: Sahih

Hadith #925 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
I heard the Messenger of Allah (ﷺ) recite in the morning prayer” Wa’l-lail-i-idhd ‘As’asa” (ixxxi. 17).
Grade: Sahih

Hadith #1822 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
In the state of the Ignorance (before embracing Islam), I used to think that the people were in error and they were not on anything (which may be called the right path) and worshipped the idols. Meanwhile, I heard of a man in Mecca who was giving news (on the basis of his prophetic knowledge) ; so I sat on my ride and went to him. The Messenger of Allah (ﷺ) was at that time hiding as his people had made life hard for him. I adopted a friendly attitude (towards the Meccans and thus managed) to
Grade: Sahih

Hadith #4985 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
While we were in a bathroom just before ‘Id al-Adha some of the persons tried to remove the hair with the help of hair-removing chemicals. Thereupon some of the people owning the bath (or some of the people sitting therein) said that Sa’id b. Musayyib did not approve of it, or he prohibited it. Then I met Sa’id b. Musayyib and made a mention of that to him, whereupon he said: O my nephew, this is the hadith which has been forgotten, and abandoned. Umm Salama, the wife of Allah’s Apostle
Grade: Sahih

Hadith #5673 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
We have accepted your allegiance, so you may go.
Grade: Sahih

Hadith #5735 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
One day when I rode behind Allah’s Messenger (ﷺ), he said (to me): Do you remember any poetry of Umayya b. Abu Salt. I said: Yes. He said: Then go on. I recited a couplet, and he said: Go on. Then I again recited a couplet and he said: Go on. I recited one hundred couplets (of his poetry). This hadith has been reported on the authority of Sharid through another chain of transmitters but with a slight variation of wording.
Grade: Sahih

Hadith #5736 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
“He (that is Umayya b. Abu Salt) was about to become a Muslim”, and in the hadith transmitted on the authority of Ibn Mahdi (the words are) “He was almost a Muslim in his poetry.”
Grade: Sahih

Hadith #6679 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
He who uttered:” There is no god but Allah, the One, having no partner with Him, His is the Sovereignty and all praise is due to Him and He is Potent over everything” ten times, he is like one who emancipated four slaves from the progeny of Isma’il. Rabi’ b. Khuthaim narrated a hadith like this. Sha’bi reported: I said to Rabi’: From whom did you hear it? He said: From ‘Amr b. Maimun. I came to ‘Amr b. Maimun and said to him: From whom did you hear this hadith? He said: from Ibn
Grade: Sahih

Hadith #7241 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
I think you have heard about the arrival of Abu `Ubaida with goods from Bahrain. They said: Allah’s Messenger, yes, it is so. Thereupon he said: Be happy and be hopeful of that which gives you delight. By Allah, it is not the poverty about which I fear in regard to you but I am afraid in your case that (the worldly) riches way be given to you as were given to those who had gone before you and you begin to vie with one another for them as they vied for them, and these may destroy you as these d
Grade: Sahih

Hadith #7402 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
‘I asked Sufyān ath-Thawrī , Shu’bah, Mālik, and Ibn Uyaynah about a man who is not reliable (Thabt) in Ḥadīth, and someone comes and asks me about him, and they said: ‘Inform against him that he is not reliable’.’
Grade: Sahih

Hadith #7434 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
‘Whoever carries arms against us then he is not from us’. said ‘Amr lied, by Allah. Rather he intended it as a way to permit his filthy opinion.’
Grade: Sahih

Hadith #7451 - Sahih Muslim - Amr bin 'Abdullah bin Abi Talha عمرو بن عبد الله بن أبي طلحة (Sahih Muslim)
‘We were near Ismā’īl bin Ulayyah, and a man narrated on authority of another man, so I said: ‘Indeed this is not reliable (Thabt)’. So the man said: ‘Are you backbiting him?’ Ismā’īl said: ‘He is not backbiting him; rather he is judging him unreliable’.
Grade: Sahih